Peranan Koperasi dalam Pemasaran Gula Kelapa Organik (Studi Kasus Koperasi Semedo Manise Sejahtera di Desa Semedo Kecamatan Pekuncen Kabupaten Banyumas) - Hidayati, Rahmah Nur; Rosyad, Anisur; Nurdiani, Ulfah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Limited marketing reach and fluctuations in coconut sugar prices are problems for coconut sugar artisans in Semedo Village, Pekuncen District, Banyumas Regency. Semedo Manise Sejahtera Cooperative is an institution that helps coconut sugar artisans in marketing coconut sugar at decent prices. This study aims to determine the role of the Semedo Manise Sejahtera Cooperative in providing market certainty, price certainty, and increasing the acceptance of coconut sugar artisans to cooperative members. The results showed that the Semedo Manise Sejahtera Cooperative succeeded in providing market certainty and price certainty to coconut sugar artisans who were members of the cooperative, but the acceptance of coconut sugar artisans members of the cooperative showed a downward trend.